Genetic diversity in maize under nitrogen restriction conditions - Weder Ferreira dos SANTOS; Flávio Sérgio AFFÉRRI; Joênes Mucci PELÚZIO; Layanni Ferreira SODRÉ; Eliane Aparecida ROTILI; Fernando Barnabé CERQUEIRA; Talita Pereira de Souza FERREIRA (Journal of Bioenergy and Food Science, 2018)
Because of the great diversity of corn genotypes and the effects of sowing seasons and nitrogenous fertilizers, in plant development, the identification of promising genotypes in these conditions allows you to provide information to determine the best strategies to be adopted in future breeding programs. Thus, this study aimed to effect of the genetic divergence among corn genotypes in different levels of nitrogen and sowing seasons in the State of Tocantins. In this sense, were conduced six maize populations of competition tests in Palmas-TO, distributed in two sowing seasons (01.21.2014 and 02.19.2014). In each sowing season, the essays were conduced under conditions of high nitrogen (N), mean and low N The experimental design used in each essay was a randomized block with three replications and 12 treatments. Genetic divergence was evaluated by method of Tocher. The characteristics ear weight with straw (Low N), humidity (Average N), number of grains in the row (High N), ear weight with straw (first and second sowing season), they are those that contributed for genetic divergence.